Waqf Governance Post-Umeed Act, 2025: Challenges and Opportunities in Contemporary India - Shalini Shukla; Chandra Prakash Singh (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
This research paper examines the transformation of India’s Waqf Act, 1995 into the UMEED (Unified Waqf Management, Empowerment, Efficiency, and Development) Act 2025, analysing its implications for religious freedom, minority rights, and federal governance in India. The study traces the historical evolution of Waqf legislation from British colonial rule through independent India, highlighting how management of Muslim religious properties has been shaped by administrative needs and political considerations. The paper reveals that while the 2025 amendment aims to modernize Waqf administration through digital systems, enhanced transparency, and professional management, it fundamentally alters the nature of community control over religious endowments. Key changes include mandatory inclusion of non-Muslim members in Waqf boards, transfer of decision-making authority from community bodies to District Collectors, elimination of traditional oral Waqf practices, and centralized digital registration requirements. The research identifies significant constitutional challenges arising from these reforms, particularly regarding religious autonomy under Article 26, minority rights under Articles 29-30, and federal structure principles. The study concludes that while the Act addresses legitimate concerns about property mismanagement and corruption, its approach may undermine constitutional protections for minority communities and disrupt the delicate balance between modern governance requirements and traditional religious practices, potentially setting precedents for future interventions in religious institutions.